2008
DOI: 10.1128/aac.01398-07
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Activity of Telavancin against Resistant Gram-Positive Bacteria

Abstract: The in vitro activity of telavancin was tested against 743 predominantly antimicrobial-resistant, gram-positive isolates. Telavancin was highly active against methicillin-resistant staphylococci (MIC 90 , 0.5 to 1 g/ml), streptococci (all MICs, <0.12 g/ml), and VanB-type enterococci (all MICs, <2 g/ml). Time-kill studies demonstrated the potent bactericidal activity of telavancin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
56
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(63 citation statements)
references
References 12 publications
7
56
0
Order By: Relevance
“…Thus the phosphonomethyl-aminomethyl substitution is expected to strengthen the face-to-face interaction. Indeed, although the affinity of vancomycin for ligand is five times greater than that of telavancin [36], the minimum inhibitory concentration values of vancomycin, THRX-689909 and telavancin to methicillin-resistant S. aureus are 1, 0.4 and 0.25 lgÁmL À1 , respectively [37,38]. This suggests that stabilizing the face-to-face dimer enhances activity.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the phosphonomethyl-aminomethyl substitution is expected to strengthen the face-to-face interaction. Indeed, although the affinity of vancomycin for ligand is five times greater than that of telavancin [36], the minimum inhibitory concentration values of vancomycin, THRX-689909 and telavancin to methicillin-resistant S. aureus are 1, 0.4 and 0.25 lgÁmL À1 , respectively [37,38]. This suggests that stabilizing the face-to-face dimer enhances activity.…”
Section: Discussionmentioning
confidence: 99%
“…Representative telavancin potency against a collection of Gram-positive clinical isolates collected from US hospitals in 2011 and 2012 is provided in TABLE 1 [23]. In addition to the international surveillance program, a number of studies have focused specifically on the activity of telavancin against Grampositive organisms with reduced susceptibility to vancomycin, with particular emphasis given to vancomycin-intermediate S. aureus (VISA) and heterogeneous VISA (hVISA) strains [24][25][26][27]. Collectively, these studies have demonstrated that telavancin possesses potent activity against VISA and hVISA, with all isolates tested remaining susceptible to telavancin according to the FDA MIC Data taken from [9,12,65].…”
Section: Microbiologymentioning
confidence: 99%
“…No other cross-resistance between telavancin and other classes of antibiotics has been identified to date. Organisms resistant to daptomycin or linezolid remain susceptible to telavancin in the FDA-approved MIC breakpoints [25]. In vitro studies of intrinsic resistance development, including both single-step and multi-passage experiments, suggest that telavancin has a low potential to select for resistance [30].…”
Section: Resistance Development Studiesmentioning
confidence: 99%
“…Non-VanA type vancomycin-resistant organisms are typically susceptible to telavancin. 9,18,19 There is no known cross-resistance between telavancin and other antibiotics. In vitro experiments have failed to generate resistance and there are no clinical reports of telavancin resistance.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…7 It has a dual mechanism of action and disrupts both cell wall synthesis and cell membrane integrity. 8 Telavancin has antimicrobial activity against a wide range of Gram-positive organisms including MRSA and some VRE [9][10][11] and has been used to treat patients with cSSSIs, [12][13][14] hospital-acquired pneumonia and ventilator-associated pneumonia. 15 In this review we will outline the mechanisms of action, antimicrobial spectrum, pharmacokinetics, clinical use and safety aspects of telavancin, and discuss its potential role in the antimicrobial armamentarium.…”
Section: Introductionmentioning
confidence: 99%